In vitro antibacterial, antioxidant and cytotoxic activity of methanol-acetone extracts from Antarctic lichens (Usnea antarctica and Usnea aurantiaco-atra) - Londoñe-Bailon, Pablo; Sánchez-Robinet, Claudia; Alvarez-Guzman, Gary (Polar Science, 2019)
The lichens are symbiotic organisms, synthesize a great variety of chemically complex. Natural and potential source of bioactive compounds. U. antarctica and U. aurantiaco-atra were collected during 23rd Peruvian Scientific Expedition (ANTAR XXIII–2015) from the Antarctic Scientific Station “Machu Picchu” and were transferred to the ITP for processing. The samples were dried and grounded, after that, an extraction with acetone (1:10 w/v) also with methanol (1:10 w/v) was performed. Both extracts were mixed and vacuumed dried (30 °C). A methanol-acetone extract (MAE) from each lichen was obtained. MAE from U. antarctica showed a major concentration of total phenols (22.80 ± 0.08 mg GA/g MAE) than U. aurantiaco-atra (19.42 ± 0.32 mg GA/g MAE). Besides, U. antarctica exhibited a superior value of inhibition of ABTS•+ radical (89.05 ± 0.01 μmol TE/g MAE) than U. aurantiaco-atra (79.84 ± 0.09 μmol TE/g MAE). The antibacterial activity of MAEs against Staphylococcus aureus ATCC 14775, Pseudomonas aeruginosa ATCC 27853 and Vibrio alginolyticus ATCC 17749 was performed however was only demonstrated against S. aureus. The minimum inhibitory concentration (MIC) was evaluated, U. antarctica and U. aurantiaco-atra exhibited 94.76% and 98.43%, respectively of inhibition bacterial growth at 31.25 μg/mL of MIC value. MAE of U. antarctica (IC50 = 169.64 μg/mL) and U. aurantiaco-atra (IC50 = 270.82 μg/mL). journal article